Potential efficacy of dopaminergic antidepressants in treatment resistant anergic-anhedonic depression results of the chronic anergic-anhedonic depression open trial – CADOT - Dormegny-Jeanjean, Ludovic Christophe; de Billy, Clément; Mainberger, Olivier; Weibel, Sébastien; Schorr, Benoit; Obrecht, Alexandre; Landré, Lionel; Berna, Fabrice; Causin, Jean-Baptiste; Blanc, Frederic; Danila, Vlad; Tomsa, Mihaela; et al. (Frontiers in Psychiatry, 2023)
Introduction Among treatment resistant depression (TRD), we identified anergic-anhedonic clinical presentations (TRAD) as putatively responsive to pro-dopaminergic strategies. Based on the literature, non-selective monoamine oxidase inhibitors (MAOI) and dopamine D2 receptor agonists (D2RAG) were sequentially introduced, frequently under the coverage of a mood stabilizer. This two-steps therapeutic strategy will be referred to as the Dopaminergic Antidepressant Therapy Algorithm (DATA). We describe short and long-term outcomes of TRAD managed according to DATA guidelines. Method Out of 52 outpatients with TRAD treated with DATA in a single expert center, 48 were included in the analysis (severity – QIDS [Quick Inventory of Depressive Symptomatology] = 16 ±3; episode’s duration = 4.1 ±2.7 years; Thase and Rush resistance stage = 2.9 ±0.6; functioning – GAF [Global Assessment of Functioning] = 41 ±8). These were followed-up for a median (1st – 3rd quartile) of 4 (1 – 9) months before being prescribed the first dopaminergic treatment and remitters were followed up 21 (11 – 33) months after remission. Results At the end of DATA step-1, 25 patients were in remission (QIDS < 6; 52% [38 – 66%]). After DATA step-2, 37 patients were in remission (77% [65 – 89%]) to whom 5 patients with a QIDS = 6 could be added (88% [78 – 97%]). Many of these patients felt subjectively remitted (GAF = 74±10). There was a significant benefit to combine MAOI with D2RAG which maintained at least 18 months in 30 patients (79% [62 – 95%]). Conclusions These results support TRAD sensitivity to pro-dopaminergic interventions. However, some clinical heterogeneities remain in our sample and suggest some improvement in the description of dopamine-sensitive form(s).